2015
DOI: 10.1007/s11128-015-1016-y
|View full text |Cite
|
Sign up to set email alerts
|

Universal quantum computation with weakly integral anyons

Abstract: Harnessing non-abelian statistics of anyons to perform quantum computational tasks is getting closer to reality. While the existence of universal anyons by braiding alone such as the Fibonacci anyon is theoretically a possibility, accessible anyons with current technology all belong to a class that is called weakly integral---anyons whose squared quantum dimensions are integers. We analyze the computational power of the first non-abelian anyon system with only integral quantum dimensions---$D(S_3)$, the quantu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 17 publications
0
43
0
Order By: Relevance
“…The modular S and T matrices of D(S 3 ) are given by [20]: where all rows and columns are ordered alphabetically, A − H, and ω = e 2πi/3 is the primitive third root of unity. and hence have no nontrivial splitting idempotents.…”
Section: 4mentioning
confidence: 99%
“…The modular S and T matrices of D(S 3 ) are given by [20]: where all rows and columns are ordered alphabetically, A − H, and ω = e 2πi/3 is the primitive third root of unity. and hence have no nontrivial splitting idempotents.…”
Section: 4mentioning
confidence: 99%
“…More precisely, we are interested in models where the square of the quantum dimensions is not an integer (compare with Theorem IV.1). Models for which the square of the quantum dimensions are integers are called weakly integral, and include quantum double models coming from groups (including the so-called twisted quantum double models) [48]. Unfortunately we do not have direct answer to this.…”
Section: Calculation Of I(a)ω For a Thin Annulusmentioning
confidence: 99%
“…For r = 2, 3, and 4 there are two-dimensional irreducible unitary representations ρ with po(ρ(σ 1 )) = r arising from weakly integral modular tensor categories. The modular tensor category structure of C = Rep D(S 3 ) was described completely in [CHW15]. The authors label the simple objects of this category with the letters A through G. It was shown that the anyon C corresponding to the standard representation of the S 3 gives rise to a unitary representation ρ C : B 3 → U(Hom(C, C ⊗3 )).…”
Section: Realization By Modular Tensor Categoriesmentioning
confidence: 99%